Akselerasi Daya Beli Masyarakat Terhadap Produk Halal Melalui E-Commerce di Provinsi Aceh - Razali, Ramadhan (Jurnal Iqtisaduna, 2021)
Aceh Province is one of the provinces in Indonesia with a majority Muslim population. The large number of people in Aceh Province who embrace Islam has implications for the large number of requests for halal needs. To meet their needs, the majority of people in Aceh Province conduct transactions through e-commerce. The purpose of this study is to discuss the phenomenon of increasing people’s purchasing power in Aceh Province through e-commerce. The type of this research is qualitative research, with descriptive analysis through secondary data. The results of this study are the increasing purchasing power of the people in Aceh Province towards the halal industry due to the effective and efficient use of e-commerce.